Media Promosi Wisata Di Boyolali Berbasis Motion Graphic - Prasetyo Punto Wicaksono; Riyan Abdul Aziz; Sri Widiyanti (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
Tourism promotion media are various facilities or platforms used to introduce, market, and advertise tourist destinations to a larger audience. The purpose of this tourism promotion media is to attract potential tourists, provide appropriate information about tourist destinations, and encourage tourists to visit Boyolali Regency. In making this promotional media using Adobe After Effects 2018 software. The design of this promotional media uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluations) method. The data collection method uses a questionnaire with seven question indicators based on questionnaire data from 40 respondents resulting in a score of 84.8%, it is concluded that this promotional video is efficient for introducing Boyolali as a tourist destination. This promotional video contains 79 tours spread across 19 sub-districts in Boyolali. This video contains brief information about all tours in Boyolali.